Resenha - Haubert, Laura Elizia; Campeotto, Fabio; Viale, Claudio Marcelo (Cognitio: Revista de Filosofia, 2020)
Resenha do libro: ARENAS, Luis; DEL CASTILLO, Ramón; FAERNA, Ángel M. (eds.) John Dewey: una estética de este mundo. Zaragoza: Prensas de la Universidad de Zaragoza, 2018, 447p. ISBN 978-84-17358-59-4